IMPLEMENTATION OF INFORMATION TECHNOLOGIES AS A HARMONIC COMPONENT OF IMPROVING THE ENVIRONMENTAL EDUCATION - Semenyuk Н.В.; Gumenyuk О.Б. (Journal of Information Technologies in Education (ITE), 2012)
The article shows author’s point of view for forming of the ecological thinking, ecological consciousness of the young generations. That is one of the main tasks on the way of overcoming of global ecological crisis. There are scientific editions and other sources on the basis of the personally conducted analysis that are specify the impotents of problem, and also attempt to find the ways of its decision and solutions. It is necessary for education system to be ready for accepting challenges of XXI centuries certain transformations of the system on the base of the use of modern information technologies.